Burials of the Early Iron Age of the Kurgans Cemetery “Bogomolnye Peski-I” - Alexey A. Timofeev; Damir S. Soloviov; Georgiy V. Stukalov; Dmitriy V. Vasiliev; Victor Yu. Bochkarev (Нижневолжский археологический вестник, 2020)
The article is dedicated to the publication of the materials of burials from the Early Iron Age, discovered during excavations of a crumbling kurgan which is a part of the cemetery “Bogomolnye Peski-I” close to the village of Nikolskoye, Enotaevsky district, Astrakhan region. In total, 14 burials were investigated during the rescue excavations, two of them relate to the Middle Ages, other seven belong to the Bronze Age. The article describes in detail 5 burials of the Early Iron Age. The dating of the burials is defined based on the materials and details of the burial rite. The earliest burial (No. 2) dates back to the Savromat era. It contained a decapitated rams carcase and a molded pot which is typical of assumed era. The rest of the burials belong to the Middle Sarmatian period (1st – 2nd centuries AD). One of the Middle Sarmatian burials was completely destroyed by robbers in ancient times. It was possible to find a lot of gold stripes of clothes among its containment, as well as a bronze cauldron with a tamga. Plaques and stripes are not typical of either the Savromat or the early Sarmatian cultures. Indeed, they are widely used in prestigious burials of the Middle Sarmatian culture. The burials No. 5 and No. 13, accompanied by a rich inventory, are of the greatest interest. A set of gold decorations for a funeral veil and a belt set of gold with turquoise inserts were found in burial No.5, which belong to the products of the Sarmatian polychrome style, typical of the Middle Sarmatian period. In addition, a gilded bronze dish related to Roman provincial dishes and an alabaster vessel were discovered there – a typical find of the Middle Sarmatian era. In burial No. 12, the most interesting findings, in addition to a large number of various beads, are intaglio gemstones made of red glass with plots of ancient mythology depicted on them, which are unique in their own way. Moreover, an interesting vessel shaped as a bird (duck) was found there as well. The close analogs to the latter are known in cemeteries of the 1st – 2nd centuries AD in the Kuban region. A feature of this kurgan is a large number of inlet burials of the Middle Sarmatian culture, whereas in general, the burials under individual mounds predominate in the Middle Sarmatian epoch.